Agenda 2030 and human rights: an analysis of the Ibero-American Literature in Library and Information Science - Gardini Santos, Joao Carlos; Martinez-Avila, Daniel; Gomes De Mello, Mariana Rodrigues [UNESP] (Ibersid Network, 2022)
The 2030 Agenda of the United Nations (UN) presents 17 Sustainable Development Goals (SDG) that can be used as a theoretical framework in scientific research. In this sense, our research question is as follows: is there a corpus of published literature in Portuguese or Spanish in the area of Library and Information Science and with an explicit mention to human rights that can be used as a theoretical reference and basis for future research on at least one of the 17 SDGs proposed by the UN in the 2030 Agenda? To answer this question, we conducted a search in the specialized database Li-brary and Information Science Abstracts (LISA) and then analyzed and categorized the retrieved docu-ments using a methodology based on Bardin. The re -sults show that after the publication of the SDGs there was a significant increase in scientific publications on sustainable development in line with human rights. SDG number 16, Promote just, peaceful and inclusive societies is the one with the highest number works on human rights. We conclude that there is a corpus of research on sustainable development in Library and In-formation Science that recognizes its importance and can be used as a background for future research deal-ing with any of the SDGs.
Keywords: Agenda 2030; Sustainable Development Goals; Human rights; Iberoamerica